2009
DOI: 10.2174/156720209787466028
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor (BDNF) has Proliferative Effects on Neural Stem Cells through the Truncated TRK-B Receptor, MAP Kinase, AKT, and STAT-3 Signaling Pathways

Abstract: Neurospheres can be generated from the mouse fetal forebrain by exposing multipotent neural stem cells (NSCs) to epidermal growth factor (EGF). In the presence of EGF, NSCs can proliferate continuously while retaining the potential to differentiate into neurons, astrocytes and oligodendrocytes. We examined the expression pattern of the neurotrophin (NT) receptors tropomysin-related kinase (TRK)-A, TRK-B, TRK-C and p75 neurotrophin receptor (p75(NTR)) in NSCs and the corresponding lineage cells. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 72 publications
3
101
0
3
Order By: Relevance
“…Due to this overall proliferative effect of BDNF on NSCs, the actual transfection efficiency reported here is therefore likely to be an underestimate of the initial transfection levels. The result here demonstrates the functional effects of the encoded BDNF as it is known to be involved in NSC proliferation, among many other cellular processes such as neural differentiation and maturation [40]. Our study shows that the BDNF levels induced are sufficient to have a functional biological effect on NSCs.…”
Section: Bdnf Overexpression Promotes Nsc Proliferationsupporting
confidence: 56%
See 1 more Smart Citation
“…Due to this overall proliferative effect of BDNF on NSCs, the actual transfection efficiency reported here is therefore likely to be an underestimate of the initial transfection levels. The result here demonstrates the functional effects of the encoded BDNF as it is known to be involved in NSC proliferation, among many other cellular processes such as neural differentiation and maturation [40]. Our study shows that the BDNF levels induced are sufficient to have a functional biological effect on NSCs.…”
Section: Bdnf Overexpression Promotes Nsc Proliferationsupporting
confidence: 56%
“…As an example, transplantation of a mixed population of VEGF-engineered NSCs (transduction efficiency of ca 20-30% obtained in this study) demonstrated neuroprotective effects and increased angiogenesis in intact non-disease brains [41]. The proliferative effects of BDNF on NSCs can be predicted to be advantageous for ex vivo gene therapy, resulting in genesis of increased numbers of progenitor populations that can in turn result in enhanced production of neurons [40]. While such enhanced division does…”
Section: Bdnf Overexpression Promotes Nsc Proliferationmentioning
confidence: 68%
“…A small population of BrdU1 cells remains unaccounted for by newly formed neurons and astrocytes suggesting that LM11A-31 promotes proliferation/survival of other cell populations; the delineation of these and determination of their roles in recovery will be the subject of future studies. Finally, it is of interest that BDNF, which has been implicated as a significant factor in TBI recovery [69] and may have direct [70] and indirect [71] effects on neural progenitors via TrkB-family receptors, was divergent from LM11A-31 and NGF in its effects on Figure 7. Controlled cortical impact (CCI) and LM11A-31 effects on spatial memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…The CellTiter-Glo ÂŽ Luminescent Cell Viability Assay (Promega, Madison, WI, USA) and the fluorescein isothiocyanate (FITC) 5-bromo-2'-deoxyuridine (BrdU) Flow Kit (BD Biosciences, Franklin Lakes, NJ, USA) were used to analyze cell proliferation as described previously (15). Briefly, the CellTiterGlo ÂŽ Luminescent Cell Viability Assay generates a luminescent signal based on the quantity of adenosine triphosphate (ATP) present in viable cells, which is proportional to the number of metabolically active cells.…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%